Nutritional Properties, Antioxidant Activity, and Consumer Acceptability of Sourdough Bread Supplemented with Marine Algae Powder Using Selected Traditional Starters - Mounir EL Boujamaai; Imane Brahimi; Meryem Benyamane; Nouhaila Belasla; João Miguel Rocha; Faouzi Errachidi; Abdellah Zinedine (Phycology)
This study aimed at producing a sourdough bread supplemented with two marine algae powders of Ulva lactuca and Gelidium corneum at 2.5, 5, 7.5, and 10% (w/w, g/100 g DW) at the laboratory scale using mixed starters prepared with three lactic acid bacteria (LAB) combinations (LCS1, LCS2, and LCS3). The phytochemical composition, nutritional value, organoleptic properties, and acceptability of algae bread by consumers were then assessed. Good results were obtained for enriched bread with Gelidium at 2.5% (GB1) with a reducing sugar of 0.77 ± 0.1%, total sugar of 36.90 ± 3.15, and protein content of 8.3 ± 0.2%. While total phenolic content was 8.32 ± 1.20 mg GAE/g DW, total flavonoids was 225.00 ± 11.31 mgQE/g DW, and the antioxidant activity ranged from 71.05 ± 3.71 to 82.93 ± 3.61%. Regarding enriched bread with Ulva at 10% (UB12), reducing sugar was 0.48 ± 0.03%, total sugar was 45.45 ± 5.75%, and protein content was 3.7 ± 0.07%. The total phenolic content value was 6.45 ± 1.19 mg GAE/g DW, total flavonoids was 191.20 ± 12.52 mgQE/g DW, while the antioxidant activity values ranged from 52.06 ± 6.21 to 80.51 ± 1.72%. Microbiological analysis showed that all pathogenic bacteria were not detected in algae bread. The consumer acceptability test revealed that bread enriched at the level of 10% of algae powder was significant for the five selected criteria (general appearance, crumb color, odor, taste, and texture). Traditional bread supplemented with Gelidium powder at 2.5% and Ulva powder at 10%, prepared with combined sourdough (LCS1), showed good antioxidant and nutritional properties and consumer acceptance.